Positive electrode material and preparation method thereof, battery and electric device
By coating the lithium iron phosphate positive electrode material with a graphene composite layer doped with lithium carbonate and boron, a solid electrolyte film is solved, and the problems of low conductivity and poor interface stability of lithium iron phosphate positive electrode material under high magnification conditions are solved. , significantly improves the battery's cycle stability and capacity retention rate.
Patent Information
- Application Number
- CN202411368116.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
AI Technical Summary
The lithium iron phosphate positive electrode material has low conductivity and poor interface stability under high magnification conditions, resulting in insufficient battery cycle stability and capacity performance. The existing carbon coating quality is poor and cannot effectively inhibit chemical mechanical degradation.
The graphene composite layer doped with lithium carbonate and boron coats the lithium iron phosphate positive electrode particles, and reacts lithium borohydride with carbon dioxide to generate lithium carbonate and boron doped graphene to form a solid electrolyte film to improve electron conductivity and ion diffusion performance. , and catalyze LiF during the battery activation stage to enhance interface stability.
It significantly improves the electronic conductivity and ion diffusion performance of lithium iron phosphate positive electrode, inhibits chemical mechanical degradation, extends the cyclic stability and capacity retention rate of the battery, and meets the power demand under high-rate charging and discharge conditions.
Smart Images

Figure CN119252922A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries, and in particular relates to a positive electrode material and a preparation method thereof, a battery, and an electrical device. Background Art
[0002] With the development of electronic products, new energy electric vehicles and energy storage industries, the requirements for batteries are gradually increasing. As the key material of the battery, the electrochemical performance of the positive electrode material has an important influence on the cycle capacity and life of the battery. The commonly used positive electrode materials are mainly lithium-containing transition metal composite oxides and lithium-containing phosphate-based materials. Among them, lithium iron phosphate is becoming the preferred solution for electric vehicles and energy storage systems due to its superior thermal stability, cost-effectiveness and breakthroughs in emerging advanced battery packaging technology. However, the inherent low electronic conductivity and ionic conductivity of lithium iron phosphate severely limit its capacity under high-rate conditions. In addition, under high-rate charge and discharge conditions, the chemical and mechanical degradation occurring on the surface and inside of the electrode will induce rapid consumption of the electrolyte, resulting in the thickening of the passivation layer on the electrode surface, reduced lithium ion diffusion, and poor long-cycle stability.
[0003] For the modification of lithium iron phosphate positive electrode, most of the current research adopts technical routes such as carbon coating, nano-sizing and element doping, among which surface carbon coating is the most common modification method. However, most of the existing research is basically focused on the preparation of a single carbon layer, mainly to improve the conductivity and ion mobility of the surface of the lithium iron phosphate positive electrode, enhance the conductivity between particles, and improve its charge and discharge capacity. However, the existing coated carbon layer has poor coating quality and insufficient coating integrity, which cannot help the lithium iron phosphate positive electrode obtain a highly stable interface structure during the electrochemical cycle, and it is difficult to suppress the problem of chemical mechanical degradation, and it is impossible to achieve excellent high-rate long-cycle performance. Therefore, the development of a simple, efficient and low-cost method to simultaneously improve the conductivity and electrochemical cycle interface stability of the lithium iron phosphate positive electrode has a very positive effect on improving the fast charge / discharge performance and service life of lithium iron phosphate batteries. Summary of the invention
[0004] In view of the problems of insufficient interface stability and conductivity of existing positive electrode active materials, the present invention provides a positive electrode material and a preparation method thereof, a battery, and an electrical device.
[0005] The technical solution adopted by the present invention to solve the above technical problems is as follows: In one aspect, the present invention provides a positive electrode material, comprising positive electrode particles and a graphene coating layer located outside the positive electrode particles, wherein the graphene coating layer is a composite layer of graphene doped with lithium carbonate and boron.
[0006] Optionally, based on the total mass of the graphene coating layer being 100%, the mass percentage of the lithium carbonate is 0.6% to 2%.
[0007] Optionally, based on the total mass of the graphene coating layer being 100%, the mass percentage of the boron is 0.2% to 0.6%.
[0008] Optionally, the thickness of the graphene coating layer is 3-20 nm.
[0009] Optionally, the positive electrode particles include positive electrode active materials, and the positive electrode active materials include one or more of lithium-containing transition metal oxides, lithium-containing phosphate-based materials, and lithium-rich manganese-based materials.
[0010] Optionally, the positive electrode active material is selected from lithium iron phosphate.
[0011] Optionally, the particle size of the positive electrode particles is 0.6~1um.
[0012] Optionally, the positive electrode particles further include a carbon coating layer, wherein the carbon coating layer is located on the outer surface of the positive electrode active material, and the graphene coating layer is located on the outer surface of the carbon coating layer.
[0013] Optionally, the carbon coating layer has a thickness of 5-10 nm.
[0014] In another aspect, the present invention provides a battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises a positive electrode material layer, and the positive electrode material layer comprises the positive electrode material as described above.
[0015] In another aspect, the present invention provides a method for preparing the positive electrode material as described above, comprising the following steps: applying lithium borohydride to the surface of the cathode particles to obtain a precursor; The precursor is placed in a protective atmosphere for heating and dehydrogenation, and then transferred to a CO2 atmosphere for reaction to obtain lithium carbonate and in-situ grown graphene, thereby obtaining a lithium carbonate and boron-doped graphene composite layer.
[0016] Optionally, the method of applying lithium borohydride to the surface of the positive electrode particles includes: dispersing lithium borohydride in a solvent to obtain a lithium borohydride solution; The lithium borohydride solution is applied to the surface of the positive electrode particles and dried to obtain a precursor.
[0017] Optionally, the mass ratio of the lithium borohydride to the positive electrode particles is 0.004-0.008:1.
[0018] Optionally, the heating temperature of the heating dehydrogenation is 600°C~700°C, and the insulation time is 5-12h.
[0019] Optionally, the heating temperature after switching to CO2 atmosphere is 250°C~400°C, and the insulation time is 1~8h.
[0020] In yet another aspect, the present invention provides an electrical device comprising the battery as described above.
[0021] According to the positive electrode material provided by the present invention, a graphene coating layer is coated on the outside of the positive electrode particles, and the graphene coating layer is a composite layer of lithium carbonate and boron-doped graphene, wherein the lithium carbonate component is in situ catalyzed by boron-doped graphene in the battery activation stage, and can react quickly with lithium hexafluorophosphate in the electrolyte to convert to LiF, prompting the positive electrode material surface to form a solid electrolyte membrane (CEI) rich in inorganic components, which can improve the electrode interface stability, inhibit the chemical mechanical degradation of the positive electrode material during the cycle, and reduce the decomposition and gas production of the electrolyte at the positive electrode interface, thereby improving the cycle stability of the positive electrode and the electrolyte. At the same time, boron-doped graphene can significantly improve the electronic conductivity and ion diffusion performance of the positive electrode material, and enhance the capacity under high-rate charge and discharge conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 XRD diagrams of Comparative Example 1 and Example 1 provided by the present invention; Figure 2 The SEM images of Comparative Example 1 and Example 1 provided by the present invention; Figure 3 TEM images of Comparative Example 1 and Example 1 provided by the present invention; Figure 4 The XPS graphs of Comparative Example 1 and Example 1 provided by the present invention; Figure 5 The resistivity diagrams of Comparative Example 1 and Example 1 provided by the present invention; Figure 6 XPS depth profiling analysis of CEI of Comparative Example 1 and Example 1 provided by the present invention; Figure 7 The long cycle test results of Comparative Example 1 and Examples 1-3 provided by the present invention at 10C. DETAILED DESCRIPTION
[0023] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0024] An embodiment of the present invention provides a positive electrode material, comprising positive electrode particles and a graphene coating layer located outside the positive electrode particles, wherein the graphene coating layer is a composite layer of graphene doped with lithium carbonate and boron.
[0025] Among them, the lithium carbonate component is in situ catalyzed by boron-doped graphene during the battery activation stage, and can react quickly with lithium hexafluorophosphate in the electrolyte to convert into LiF, prompting the formation of a solid electrolyte membrane (CEI) rich in inorganic components on the surface of the positive electrode material. This solid electrolyte membrane can improve the stability of the electrode interface, inhibit the chemical and mechanical degradation of the positive electrode material during the cycle, and reduce the decomposition and gas production of the electrolyte at the positive electrode interface, thereby improving the cycle stability of the positive electrode and the electrolyte. At the same time, boron-doped graphene can significantly improve the electronic conductivity and ion diffusion performance of the positive electrode material, and enhance the capacity under high-rate charge and discharge conditions.
[0026] In some embodiments, the graphene coating layer is coated on part or all of the surface of the positive electrode particles.
[0027] Based on the gain effect of the graphene coating on the positive electrode material, as the coverage rate of the graphene coating on the positive electrode particles increases, it is beneficial to improve the cycle stability and electronic conductivity of the positive electrode particles. In some embodiments, the coverage rate of the graphene coating on the positive electrode particles (calculated as a percentage of the covered surface area) is 50% or more. Preferably, the coverage rate of the graphene coating on the positive electrode particles is 80% or more. More preferably, the coverage rate of the graphene coating on the positive electrode particles is 95% or more. More preferably, the coverage rate of the graphene coating on the positive electrode particles is 99% or more.
[0028] In some embodiments, based on the total mass of the graphene coating layer being 100%, the mass percentage of the lithium carbonate is 0.6% to 2%.
[0029] As described in the following preparation method, the lithium carbonate is obtained by reacting lithium hydride generated by dehydrogenation of lithium borohydride with carbon dioxide. Therefore, the content of lithium carbonate in the generated graphene coating layer can be regulated by controlling the amount of lithium borohydride added, the concentration of carbon dioxide and the reaction conditions (temperature, time, etc.). The lithium carbonate participates in the formation of inorganic components in the positive electrode surface solid electrolyte membrane (CEI) during the subsequent battery activation process, and has a great influence on the construction of a stable CEI structure. When the content of lithium carbonate in the graphene coating layer is within the above range, it is beneficial to improve the stability and integrity of the positive electrode surface solid electrolyte membrane (CEI).
[0030] In some embodiments, based on the total mass of the graphene coating layer being 100%, the mass percentage of the boron is 0.2% to 0.6%.
[0031] Boron, as a p-type dopant, can increase the hole concentration, thereby improving the conductivity of the graphene coating layer. Furthermore, boron-doped graphene is beneficial to catalyze the conversion of lithium carbonate components in the battery activation stage and is beneficial to the construction of a solid electrolyte membrane (CEI) on the positive electrode surface. When the mass percentage of boron in the graphene coating layer is within the above range, it is beneficial to ensure that the graphene coating layer has better electronic conductivity and a protective effect on the positive electrode material.
[0032] In some embodiments, the graphene coating layer has a thickness of 3 to 20 nm.
[0033] In a specific embodiment, the thickness of the graphene coating layer can be 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm or 20nm.
[0034] When the graphene coating layer is within the above thickness range, on the one hand, it is beneficial to improve the electronic conductivity of the positive electrode material and provide a basis for the subsequent construction of the positive electrode surface solid electrolyte membrane (CEI); on the other hand, it also avoids the influence of the graphene coating layer being too thick on the ion conduction between the positive electrode material and the electrolyte.
[0035] In some embodiments, the positive electrode particles include a positive electrode active material, and the positive electrode active material includes one or more of a lithium-containing transition metal oxide, a lithium-containing phosphate-based material, and a lithium-rich manganese-based material.
[0036] The lithium-containing transition metal oxide includes one or more of lithium cobalt oxide, lithium nickel manganese cobalt oxide, lithium nickel cobalt aluminum oxide, and lithium manganese oxide; the lithium-containing phosphate-based material includes lithium iron phosphate; and the lithium-rich manganese-based material includes Li2MnO3.
[0037] It should be noted that, in some embodiments, the above positive electrode active materials can be doped with other metal elements or non-metal elements to obtain a more stable structure, and the doped elements include but are not limited to one or more of B, Ga, F, W, Zr, Mg, Na, Pb, K, Al, Cr, Ba, Ca, Ni, Sr, Ti, Zn, Si, V, Mo, Nb, S, N, F, B, Cl, Br and I.
[0038] In a preferred embodiment, the positive electrode active material is selected from lithium iron phosphate.
[0039] Since the graphene coating layer provided by the present invention has a significant improvement in the electronic conductivity and structural stability of the positive electrode active material, this positive electrode material coating layer structure is more suitable for positive electrode active materials with low intrinsic conductivity. When the positive electrode active material is selected from lithium iron phosphate, it can better overcome the problems of low conductivity and insufficient cycle stability of lithium iron phosphate, and achieve better electrochemical performance improvement effect.
[0040] In some embodiments, the particle size of the positive electrode particles is 0.6~1um.
[0041] In some embodiments, the positive electrode particles further include a carbon coating layer, the carbon coating layer is located on the outer surface of the positive electrode active material, and the graphene coating layer is located on the outer surface of the carbon coating layer.
[0042] The carbon coating layer is used to improve the electronic conductivity of the positive electrode active material, but the carbon coating layer prepared by the traditional method has the problem of uneven coating and exposure of the positive electrode active material in some positions, and the protective effect on the positive electrode active material is limited. By compounding the graphene coating layer, on the one hand, the electronic conductivity is further improved, and on the other hand, it is conducive to the comprehensive coating of the positive electrode active material, while promoting the construction of the solid electrolyte membrane (CEI) and improving the protective effect on the positive electrode active material.
[0043] In some embodiments, the carbon coating layer has a thickness of 5-10 nm.
[0044] It should be noted that, in some optional embodiments, the carbon coating layer may be optional, that is, the positive electrode particles do not include a carbon coating layer, and the graphene coating layer prepared by the present invention replaces the carbon coating layer.
[0045] Another embodiment of the present invention provides a battery, including a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode includes a positive electrode material layer, and the positive electrode material layer includes the positive electrode material as described above.
[0046] By coating the surface of the positive electrode particles with a composite layer of lithium carbonate and boron-doped graphene, the electronic conductivity and ion diffusion performance of the positive electrode material can be significantly improved, and a stable CEI structure can be constructed during the electrochemical process, so that the positive electrode material exhibits good high-rate and long-cycle performance, which can meet the power requirements of hybrid vehicles in low-power scenarios.
[0047] In some embodiments, the positive electrode material layer further includes a positive electrode binder and a positive electrode conductor, and the positive electrode active material, the positive electrode binder and the positive electrode conductor are blended to obtain the positive electrode material layer.
[0048] The positive electrode binder includes polyvinylidene fluoride, a copolymer of vinylidene fluoride, polytetrafluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene, a copolymer of tetrafluoroethylene-hexafluoropropylene, a copolymer of tetrafluoroethylene-perfluoroalkyl vinyl ether, a copolymer of ethylene-tetrafluoroethylene, a copolymer of vinylidene fluoride-tetrafluoroethylene, a copolymer of vinylidene fluoride-trifluoroethylene, a copolymer of vinylidene fluoride-trichloroethylene, a copolymer of vinylidene fluoride-fluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, a thermoplastic resin such as polyethylene and polypropylene; an acrylic resin; and at least one of styrene butadiene rubber.
[0049] The positive electrode conductive agent includes at least one of conductive carbon black, conductive carbon balls, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene or reduced graphene oxide.
[0050] In some embodiments, the positive electrode also includes a positive electrode current collector, the positive electrode material layer covers the surface of the positive electrode current collector, and the positive electrode current collector includes a metal material that can conduct electrons. Preferably, the positive electrode current collector includes at least one of Al, Ni, tin, copper, and stainless steel. In a more preferred embodiment, the positive electrode current collector is selected from aluminum foil.
[0051] In some embodiments, the negative electrode includes a negative electrode active material, and the negative electrode active material includes at least one of artificial graphite, natural graphite, silicon-based negative electrode, tin-based negative electrode, and lithium negative electrode. Among them, the silicon-based negative electrode may include silicon materials, silicon oxides, silicon-carbon composite materials, and silicon alloy materials; the tin-based negative electrode may include tin, tin carbon, tin oxygen, and tin metal compounds; the lithium negative electrode may include metallic lithium or lithium alloys. The lithium alloy may specifically be at least one of lithium silicon alloy, lithium sodium alloy, lithium potassium alloy, lithium aluminum alloy, lithium tin alloy, and lithium indium alloy.
[0052] In some embodiments, the electrolyte includes one or more of a solid electrolyte, a semi-solid electrolyte, a gel electrolyte, and an electrolyte solution.
[0053] Another embodiment of the present invention provides a method for preparing the positive electrode material as described above, comprising the following steps: applying lithium borohydride to the surface of the cathode particles to obtain a precursor; The precursor is placed in a protective atmosphere for heating and dehydrogenation, and then transferred to a CO2 atmosphere for reaction to obtain lithium carbonate and in-situ grown graphene, thereby obtaining a lithium carbonate and boron-doped graphene composite layer.
[0054] The preparation principle of the lithium carbonate and boron doped graphene composite layer is as follows: during the heating dehydrogenation process, lithium borohydride is thermally decomposed to remove part of the hydrogen to form hydrogen gas, and lithium hydride and boron are formed at the same time; when switched to a CO2 atmosphere, CO2 is reduced by lithium hydride on the surface of the precursor and grows in situ to form graphene and lithium carbonate, and finally a lithium carbonate and boron doped graphene composite layer is obtained.
[0055] It should be noted that in the present preparation method, the heating dehydrogenation process and the subsequent transfer to a CO2 atmosphere for graphene preparation are both necessary processes for forming a lithium carbonate and boron doped graphene composite layer. Combining the two or reversing the order will result in changes in the product, and thus a lithium carbonate and boron doped graphene composite layer cannot be prepared.
[0056] In some embodiments, the method of applying lithium borohydride to the surface of the positive electrode particles comprises: dispersing lithium borohydride in a solvent to obtain a lithium borohydride solution; The lithium borohydride solution is applied to the surface of the positive electrode particles and dried to obtain a precursor.
[0057] By treating the positive electrode particles with a lithium borohydride solution, it can be ensured that the lithium borohydride solution is evenly distributed on the surface of the positive electrode particles, thereby achieving complete coating of the positive electrode particles and protecting the positive electrode particles.
[0058] The solvent may be selected from solvents that do not react with lithium borohydride. In one embodiment, the solvent is selected from tetrahydrofuran.
[0059] In some embodiments, the drying method is: heating to 90° C. to 150° C. under a protective atmosphere to evaporate the solvent to obtain a precursor.
[0060] In the description of the present invention, the protective atmosphere refers to a gas that does not participate in the reaction, which can avoid the influence of reactive gases such as oxygen on the reaction process. As an example of the protective atmosphere, it can be an inert gas, etc.
[0061] In some embodiments, the mass ratio of the lithium borohydride to the positive electrode particles is 0.004-0.008:1.
[0062] In some embodiments, the heating temperature of the heating dehydrogenation is 600° C. to 700° C., and the holding time is 5 to 12 hours.
[0063] In the process of heating dehydrogenation, if the heating temperature is too low, it is difficult to ensure the decomposition and dehydrogenation of lithium borohydride; if the heating temperature is too high, it is easy to induce unnecessary side reactions, which is also not conducive to the decomposition and dehydrogenation of lithium borohydride.
[0064] In some embodiments, the heating temperature after switching to CO2 atmosphere is 250°C~400°C, and the holding time is 1~8h.
[0065] In the process of switching to CO2 atmosphere for the preparation of graphene and lithium carbonate, if the heating temperature is too low, it will easily lead to low graphene preparation efficiency; if the heating temperature is too high, it will cause side reactions and affect the preparation of lithium carbonate and boron-doped graphene composite layers.
[0066] In some embodiments, the positive electrode particles include a positive electrode active material and a carbon coating layer coated on the surface of the positive electrode active material.
[0067] The positive electrode particles can be commercially available or homemade.
[0068] In some embodiments, the carbon coating layer can be prepared by the following method: 1. Direct mixing of carbon sources: In the process of synthesizing positive electrode active materials, the carbon source (such as glucose, sucrose, citric acid, polyvinyl alcohol, etc.) is directly mixed with the positive electrode active material precursor (iron source, phosphorus source), and the carbon source is decomposed by high-temperature sintering or calcination to form a carbon coating layer.
[0069] 2. Hydrothermal method: The positive electrode active material precursor is mixed with the carbon source in an autoclave, and the carbon source is evenly distributed through a hydrothermal reaction to finally form a carbon coating layer.
[0070] 3. Chemical Vapor Deposition: By exposing the positive electrode active material particles to a gas environment containing a carbon source (such as methane, ethanol vapor, etc.), carbon is deposited on the surface of the LFP particles under high temperature conditions to form a carbon coating layer.
[0071] 4. Sol-Gel Method: The carbon source is converted into a carbon coating layer by mixing the carbon source with the sol to form a gel and then performing heat treatment.
[0072] 5. Self-propagating high temperature synthesis (SHS): A carbon source is added to the precursor of the positive electrode active material, and through a self-propagating high-temperature synthesis reaction, the carbon source forms a carbon coating layer in the process of rapid heating and self-propagating combustion.
[0073] 6. Co-precipitation method: A carbon source is added during the co-precipitation process of the positive electrode active material precursor, the carbon source is evenly dispersed in the precursor through a co-precipitation reaction, and then a carbon coating layer is formed through high-temperature treatment.
[0074] 7. Self-assembly method: With the help of surfactants or templates, the carbon source is self-assembled on the surface of LFP particles to form a carbon coating layer.
[0075] 8. Electrochemical deposition method: A layer of carbon material is deposited on the surface of the positive electrode active material through electrochemical deposition technology to form a carbon coating layer.
[0076] Another embodiment of the present invention provides an electric device, comprising the battery as described above.
[0077] The present invention is further described below by way of examples.
[0078] Example 1 This embodiment is used to illustrate the positive electrode material and the preparation method thereof disclosed in the present invention, and includes the following steps: In a 0.1MPa argon glove box, lithium borohydride and lithium iron phosphate powder were weighed at a mass ratio of 0.004:1 and placed in glass bottles. The lithium iron phosphate powder was commercially available and included lithium iron phosphate particles and a carbon coating layer coated on the surface of the lithium iron phosphate particles. The lithium borohydride was dissolved in tetrahydrofuran to obtain a lithium borohydride solution, and the lithium iron phosphate powder was added thereto and stirred for 20 minutes. It was then heated and dried at 100°C to obtain a precursor.
[0079] The precursor was placed in a tubular furnace and heated to 640°C at a heating rate of 5K / min under an argon atmosphere and kept warm for 12 hours. It was then switched to a CO2 atmosphere and kept warm at 300°C for 8 hours to obtain a lithium iron phosphate positive electrode coated with a lithium carbonate / boron-doped graphene composite layer.
[0080] Example 2 This embodiment is used to illustrate the positive electrode material and the preparation method thereof disclosed in the present invention, and includes the following steps: In a 0.1MPa argon glove box, lithium borohydride and lithium iron phosphate powder were weighed in a mass ratio of 0.006:1 and placed in glass bottles. The lithium iron phosphate powder was commercially available and included lithium iron phosphate particles and a carbon coating layer coated on the surface of the lithium iron phosphate particles. The lithium borohydride was dissolved in tetrahydrofuran to obtain a lithium borohydride solution, and the lithium iron phosphate powder was added thereto and stirred for 20 minutes. It was then heated and dried at 100°C to obtain a precursor.
[0081] The precursor was placed in a tubular furnace and heated to 700°C at a heating rate of 5K / min under an argon atmosphere and kept warm for 5 hours. It was then switched to a CO2 atmosphere and kept warm at 300°C for 1 hour to obtain a lithium iron phosphate positive electrode coated with a lithium carbonate / boron-doped graphene composite layer.
[0082] Example 3 This embodiment is used to illustrate the positive electrode material and the preparation method thereof disclosed in the present invention, and includes the following steps: In a 0.1MPa argon glove box, lithium borohydride and lithium iron phosphate powder were weighed at a mass ratio of 0.008:1 and placed in glass bottles. The lithium iron phosphate powder was commercially available and included lithium iron phosphate particles and a carbon coating layer coated on the surface of the lithium iron phosphate particles. The lithium borohydride was dissolved in tetrahydrofuran to obtain a lithium borohydride solution, and the lithium iron phosphate powder was added thereto and stirred for 20 minutes. It was then heated and dried at 100°C to obtain a precursor.
[0083] The precursor was placed in a tubular furnace and heated to 600°C at a heating rate of 5K / min under an argon atmosphere and kept warm for 12 hours. It was then switched to a CO2 atmosphere and kept warm at 300°C for 8 hours to obtain a lithium iron phosphate positive electrode coated with a lithium carbonate / boron-doped graphene composite layer.
[0084] Comparative Example 1 This comparative example directly uses lithium iron phosphate powder as the positive electrode material. The lithium iron phosphate powder includes lithium iron phosphate particles and a carbon coating layer coated on the surface of the lithium iron phosphate particles.
[0085] Performance Testing 1. X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and resistivity test were performed on the positive electrode material obtained in Example 1 and the positive electrode material obtained in Comparative Example 1, respectively. The test results are as follows: Figure 1~Figure 5 shown.
[0086] in, Figure 1 1 is the XRD diagram of Comparative Example 1 and Example 1; Figure 2 The SEM images of Comparative Example 1 and Example 1 (a and c are Comparative Example 1, b and d are Example 1).
[0087] Depend on Figure 1 and Figure 2 It can be seen from the test results that both Comparative Example 1 and Example 1 belong to the Pnma space group structure, the unit cell parameters of the two have basically not changed, and the particle morphology and particle size of the two are similar, indicating that the lithium carbonate / boron-doped graphene composite layer coating does not change the crystal structure of lithium iron phosphate.
[0088] Figure 3TEM images of Comparative Example 1 and Example 1 (a and b are Comparative Example 1, c and d are Example 1); Depend on Figure 3 The test results show that the surface of the original lithium iron phosphate particles in comparative example 1 has a sporadic distribution of flocculent carbon layers, and a large amount of the surface is exposed. In contrast, a continuous, thin and dense coating layer is formed on the surface of Example 1, and its thickness is about 3-5nm. High-resolution transmission electron microscopy (HRTEM) shows that the coating layer is a lithium carbonate / boron-doped graphene composite structure.
[0089] Figure 4 The XPS graphs of Comparative Example 1 and Example 1 provided by the present invention.
[0090] Depend on Figure 4 The test results show that compared with Comparative Example 1, Example 1 has two new C1 s Peak (sp 3 CC ~ 285.3 eV and BC ~ 284.3 eV) and three new B1 s Peaks (BCO2~ 192.4 eV, BC2O~190.6 eV and BC3~189.4 eV) confirm the characteristics of boron-doped graphene in the composite coating. At the same time, Example 1 also showed enhanced intensity at CO (C1s: 286.5 eV; O1s: 532.2 eV) and OC=O (C1s: 289.1 eV; O1s: 533.6 eV), and a Li2CO3 peak (54.6 eV) appeared in the Li 1s spectrum, confirming the presence of Li2CO3 in the composite coating.
[0091] Figure 5 The resistivity diagrams of Comparative Example 1 and Example 1 provided by the present invention.
[0092] Depend on Figure 5 It can be seen from the test results that Example 1 has a smaller resistivity value than Comparative Example 1, indicating that its conductivity is higher.
[0093] 2. The following performance tests were performed on the positive electrode materials provided in the above-mentioned Examples 1 to 3 and Comparative Example 1: The obtained positive electrode material was mixed with conductive carbon black C45 and binder PVDF in a mass ratio of 8:1:1, and then the prepared lithium iron phosphate positive electrode slurry was coated on aluminum foil and dried at 80°C in a vacuum drying oven for 12 hours to obtain a positive electrode sheet. In a glove box with moisture and oxygen below 0.1 ppm, the glove box was filled with argon, a lithium sheet was used as the negative electrode, an electrolyte of 1 mol / LLiPF6 (solvent EC:DEC=1:2 Vol%, 10% FEC) was added, and a PP / PE / PP composite separator with a thickness of 25μm was used to assemble a CR2025 button cell.
[0094] The battery was activated for 3 cycles by charging to 4.2 V at a constant current of 0.1 C and then discharging to 2.5 V at a constant current. The battery was then tested for 1000 cycles by charging to 4.2 V at a constant current of 10 C and then discharging to 2.5 V at a constant current.
[0095] The activated batteries of Example 1 and Comparative Example 1 were disassembled, and the positive electrodes were extracted for X-ray photoelectron spectroscopy (XPS) testing. The test results are as follows: Figure 6 (a is comparative example 1, b is example 1) as shown.
[0096] from Figure 6 It can be seen that compared with Comparative Example 1, the positive electrode of Example 1 presents a more obvious LiF-rich CEI structure both in the inner layer and the outer layer, which indicates that the boron-doped graphene effectively catalyzes the conversion of Li2CO3 into LiF, thereby enabling the CEI to obtain higher mechanical strength and stability.
[0097] Figure 7The long cycle test results of Comparative Example 1, Example 1, Example 2 and Example 3 at 10C. It can be seen that after three cycles of activation at 0.1C, the initial discharge specific capacities of the comparative example, Example 1, Example 2 and Example 3 at a rate of 10C are 94mAh / g, 113.2mAh / g, 107.3mAh / g and 112.9mAh / g, respectively. The initial discharge specific capacities of the three groups of embodiments are significantly higher than that of Comparative Example 1. After the capacity stabilizes after a certain number of cycles, the capacity gap between the embodiment and the comparative example is further widened. After 500 cycles, the discharge specific capacities of Examples 1-3 are 102.1mAh / g, 96.8mAh / g and 104.7mAh / g, respectively, which are better than 75.6mAh / g of Comparative Example 1. After 1000 cycles, the discharge specific capacities of Examples 1-3 were 99.6 mAh / g, 93.3 mAh / g and 101.1 mAh / g, respectively, and the capacity retention rates were 88.0%, 87.0% and 89.6%, respectively. In comparison, the discharge specific capacity of Comparative Example 1 was 60.7 mAh / g, and the capacity retention rate was only 64.6%. Obviously, after being coated with the lithium carbonate / boron-doped graphene composite layer, the high-rate long-cycle stability of the lithium iron phosphate positive electrode was significantly improved.
[0098] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A positive electrode material, characterized in that: It comprises positive electrode particles and a graphene coating layer located outside the positive electrode particles, wherein the graphene coating layer is a graphene composite layer doped with lithium carbonate and boron.
2. The positive electrode material according to claim 1, characterized in that Taking the total mass of the graphene coating layer as 100%, the mass percentage of the lithium carbonate is 0.6% to 2%.
3. The positive electrode material according to claim 1, characterized in that Taking the total mass of the graphene coating layer as 100%, the mass percentage of the boron is 0.2% to 0.6%.
4. The positive electrode material according to claim 1, characterized in that The thickness of the graphene coating layer is 3-20 nm.
5. The positive electrode material according to claim 1, characterized in that The positive electrode particles include positive electrode active materials, and the positive electrode active materials include one or more of lithium-containing transition metal oxides, lithium-containing phosphate-based materials, and lithium-rich manganese-based materials.
6. The positive electrode material according to claim 5, characterized in that The positive electrode active material is selected from lithium iron phosphate.
7. The positive electrode material according to any one of claims 1 to 6, characterized in that The particle size of the positive electrode particles is 0.6-1 um.
8. The positive electrode material according to claim 5, characterized in that The positive electrode particles further include a carbon coating layer, wherein the carbon coating layer is located on the outer surface of the positive electrode active material, and the graphene coating layer is located on the outer surface of the carbon coating layer.
9. The positive electrode material according to claim 8, characterized in that The thickness of the carbon coating layer is 5-10 nm.
10. A battery, characterized in that: The invention comprises a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises a positive electrode material layer, and the positive electrode material layer comprises the positive electrode material according to any one of claims 1 to 9.
11. The method for preparing a positive electrode material according to any one of claims 1 to 9, characterized in that: The steps include: applying lithium borohydride to the surface of the cathode particles to obtain a precursor; The precursor is placed in a protective atmosphere for heating and dehydrogenation, and then transferred to a CO2 atmosphere for reaction to obtain lithium carbonate and in-situ grown graphene, thereby obtaining a lithium carbonate and boron-doped graphene composite layer.
12. The method for preparing the positive electrode material according to claim 11, characterized in that: Methods for applying lithium borohydride to the surface of positive electrode particles include: dispersing lithium borohydride in a solvent to obtain a lithium borohydride solution; The lithium borohydride solution is applied to the surface of the positive electrode particles and dried to obtain a precursor.
13. The method for preparing the positive electrode material according to claim 11 or 12, characterized in that: The mass ratio of the lithium borohydride to the positive electrode particles is 0.004-0.008:
1.
14. The method for preparing the positive electrode material according to claim 11, characterized in that: The heating temperature of heating dehydrogenation is 600℃~700℃, and the insulation time is 5-12h.
15. The method for preparing the positive electrode material according to claim 11, characterized in that: The heating temperature after switching to CO2 atmosphere is 250℃~400℃, and the holding time is 1~8h.
16. An electrical device, characterized in that: Comprising the battery as claimed in claim 10.
Citation Information
Patent Citations
Preparation method for carbon-graphene doubly modified lithium iron phosphate anode material
CN104600292A
Cathode material for lithium ion battery and preparation method thereof
CN106531998A
Heteroatom doped graphene coated composite electrode material and preparation method thereof
CN107221666A
Positive electrode material and preparation method and application thereof
CN113764630A
Boron-doped reduced graphene oxide coated lithium manganese iron phosphate composite material and preparation method thereof
CN116190612A
